Serotype distribution and incidence of invasive early onset and late onset group B streptococcal disease amongst infants in Singapore - Kam, Kai-Qian (2022)
Background: The current group B streptococcal (GBS) preventive measures had reduced invasive GBS early onset disease (EOD) incidences worldwide, but the late onset disease (LOD) incidences had remained unchanged. Administration of a safe and effective GBS vaccine in addition to the current strategies were thought to be the next steps in reducing the incidences of invasive GBS infection especially LOD. In this study, we aimed to examine the causative GBS serotypes in invasive GBS disease, determine the incidences of EOD and LOD, and compare the risk factors between EOD and LOD. Methods: A retrospective study of infants ≤90-day-old over an 8-year period (2010–2017). The incidences of EOD and LOD were obtained by using patients with EOD and LOD who were born in our institution as the numerator and the live births in our institution per year of the study period as the denominator. Available GBS isolates were serotyped by the National Public Health Laboratory using capsular serotyping methods. The risk factors of EOD and LOD were compared. Results: A total of 71 infants were identified; 16 (22.5%) and 55 (77.5%) of them had EOD and LOD, respectively. Serotype III (n=42, 71.2%) was the most common serotype amongst the 59 isolates available for serotyping. Serotypes Ia, Ib, II, III, and V accounted for 98.3% (n=58) of the invasive GBS diseases. The overall incidence was 0.42 per 1000 live births. The mean incidences of EOD and LOD were 0.13 per 1000 live births and 0.29 per 1000 live births, respectively. On multivariate analysis, risk factors for LOD as compared to EOD were: Chinese ethnicity (OR 27.1, 95% CI 3.0–243.1, p=0.003) and negative/unknown maternal GBS status (OR 20.0, 95% CI 2.0–250.0, p=0.012). Prematurity and intra partum risk factors (peripartum maternal pyrexia, prolonged rupture of membrane) of EOD were not associated with LOD. Conclusions: The LOD incidence had remained higher than EOD incidence in our cohort. A GBS vaccine that covers the major causative serotypes found in our cohort can potentially reduce the overall GBS disease burden in the country.